Global wine markets, 1860 to 2016: A statistical compendium - Kym Anderson; Signe Nelgen; Vicente Pinilla Navarro (University of Adelaide Press, 2017)
Until recently, most grape-based wine was consumed close to where it was produced, and mostly that was in Europe. Now more than two-fifths of all wine consumed globally is produced in another country, including in the Southern Hemisphere, the USA and Asia. This latest edition of global wine statistics not only updates data to 2016 but also adds another century of data. The motivation to assemble those historical data was to enable comparisons between the current and the previous globalization waves. This unique database reveals that, even though Europe's vineyards were devastated by vine diseases and the pest phylloxera from the 1860s, most "New World" countries remained net importers of wine until late in the nineteenth century. Some of the world's leading wine economists and historians have contributed to and drawn on this database to examine the development of national wine market developments before, during and in between the two waves of globalization. Their initial analyses cover all key wine-producing and -consuming countries using a common methodology to explain long-term trends and cycles in national wine production, consumption, and trade.
Keywords: 330; global wine markets; statistical compendium; kym anderson; signe nelgen; vicente pinilla; wine and wine making; statistics; wine industry; globalisation; economic aspects; new world wine; global wine trade; australian market; south american market; american market; asian market; european market; global wine statistics; excise; import tax; domestic sales; overseas sales; per capita expenditure; national markets; wine brand; wine brands; unit value of wine production; wine consumption; exports; imports; non-premium wine; commercial-premium wine; super-premium wine